Summer Grazing of Steers in Eastern Kansas - Jones, Rodney; Dhuyvetter, Kevin C. (My University, 1998)
This publication is a guide to budget estimates costs and returns for a season-long and an early-intensive grazing system in Eastern, KS.
MF1008_1998-10
Keywords: MF1008; Economics; Livestock; MF